Eros Beyond the Death Drive. - Martínez Ruiz, Rosaura (Fordham University Press, 2021)
This book elaborates the political and intimate possibilities of going beyond the tendency toward destruction that Freud identified in human nature. Martínez argues that Eros is the force that can help us resist this destructive drive, and that resistance must take the form of unceasing ethical vigilance and political action.